Perancangan Dashboard Monitoring dan Evaluasi Data Mahasiswa Jurusan Teknologi Informasi menggunakan Metode Design Thinking - Astiningrum, Mungki; Vista, Candra Bella; Wakhidah, Rokhimatul (Institut Teknologi Adhi Tama Surabaya, 2025)
Data is the most valuable commodity. Data management is not only a necessity but also a crucial foundation in responding to and optimizing the potential of an organization, including the Information Technology Department of Malang State Polytechnic. The Information Technology Department has a data volume continues to increase significantly, one related to student data. No system can display student data concisely, making the monitoring and evaluation process difficult, for such as accreditation. The development of a dashboard for monitoring and evaluating student data in the Information Technology Department is a strategic step to increase the effectiveness of data management. The dashboard provides a visualization interface that allows for fast and efficient data monitoring and analysis. This study uses the design thinking method. This approach is suitable because users are involved in ensuring that the dashboard is designed according to needs so that it can support data-based decision-making. The user acceptance test method aims to assess several parameters, including information, design, use, and user loyalty. The test results showed that 89% of respondents agreed that the dashboard was considered feasible and met the assessment criteria based on the parameters tested.